Multifunctional Biocompatible Nanoparticles: Surface Modification and Synthesis of Layered Double Hydroxides for Biomedical Applications - Chandrawanshi, Dr. Ekta; Pandey, Dr. Preeti (Migration Letters, 2023)
Layered Double Hydroxides (LDHs) are considered versatile materials owing to their distinctive features resulting from the isomorphous substitution of metal cations, namely M(II) and M(III), inside their octahedral locations. The LDH layer structure is characterized by a balanced arrangement of exchangeable hydrated or solvated anions within the interlayer and outer regions. This arrangement gives rise to a two-dimensional heterostructure with an ABAB pattern. Various metal cations have a role in LDHs composition, leading to their classification as hydrocalumites and hydrotalcite. Pristine-LDHs that include diverse inorganic anions have shown significant potential in biological applications. These substances have been investigated for their potential use in many applications, including but not limited to antacids, vaccination adjuvants, etc. The attainment of monodispersity in the size of LDHs is of utmost importance for their efficacy in biomedicine. This research emphasizes that the potential of LDHs is contingent upon effectively resolving difficulties, including those associated with size polydispersity. This study suggests using Surface Modified and Synthesized Layered Double Hydroxides for Biomedical Applications (SMS-LDH-BMA). The present study presents a novel approach that incorporates various enhancements, such as a decreased hydrodynamic diameter of 44.6 nm, a zeta potential of -23.86 mV, a high encapsulation efficiency of 91.2%, a substantial drug loading capacity of 14.6%, a favorable cell viability of 96.44%, and a controlled release rate of GLIB at 3.73 μg/mL/min. These findings demonstrate the efficacy of SMS-LDH-BMA in tackling these obstacles and augmenting the drug delivery capabilities and biomedical applications of LDHs.